Brain circuitries involved in emotional interference task in major depression disorder - Chechko, Natalia; Augustin, Marc; Zvyagintsev, Michael; Schneider, Frank; Habel, Ute; Kellermann, Thilo (Journal of affective disorders, 2013)
Emotional and non-emotional Stroop are frequently applied to study major depressive disorder (MDD). The versions of emotional Stroop used in previous studies were not, unlike the ones employed in the present study, based on semantic incongruence, making it difficult to compare the tasks. We used functional magnetic resonance imaging (fMRI) to study the neural and behavioral responses of 18 healthy subjects and 18 subjects with MDD to emotional and non-emotional word-face Stroop tasks based on semantic incompatibility between targets and distractors. In both groups, the distractors triggered significant amounts of interference conflict. A between-groups comparison revealed hypoactivation in MDD during emotional task in areas supporting conflict resolution (lateral prefrontal cortex, parietal and extrastriate cortices) paralleled by increased response in the right amygdala. Response in the amygdala, however, did not vary between conflicting and non-conflicting trials. While in the emotional (compared to non-emotional) task healthy controls showed considerably stronger involvement of networks related to conflict resolution, in patients, the processing differences between the two conflict types were negligible. The patients group was inhomogeneous in terms of medication and clinical characteristics. The number of female participants was higher, due to which gender effects could not be studied or excluded. Whilst healthy controls seemed able to adjust the involvement of the network supporting conflict resolution based on conflict demand, patients appeared to lack this capability. The reduced cortical involvement coupled with increased response of limbic structures might underlie the maladjustment vis-à-vis new demands in depressed mood.